Coherence and disparity in assessment literacies among higher education staff (UCL Press, 2018)
Assessment literacies are finding leverage, but there is little exploration of links between theory, practice and perceived understandings in higher education (HE). This article builds on and consolidates research that has taken place over ten years that evaluates assessment literacies among HE lecturers in education and science, and in staff developers, by presenting a comparative view of the data. The results indicate that there was generally a good understanding of theoretical and practical aspects of summative assessment across all groups. However, understandings of formative assessment showed little concordance between and within the groups, particularly among staff developers, but this group was better at clarifying the necessary link between formative assessment and feedback. Although education lecturers had a firmer grasp of central terminologies, in general there are still deficits in understanding about how these terms interrelate. Staff developers' relative weakness of understanding in some areas is of concern since this group shapes those who teach. These issues are exacerbated by a lack of acknowledgement that they exist, which may seriously hamper the development of both staff and students in clarifying processes they encounter daily. Basic shared understandings are required that can translate into personal, coherent assessment literacies. As a community we need to take on this task, because if we do not, as individuals, or individual groups, we will continue to have fragmented assessment literacies.